Freeze-thaw cycles and snow impact at arid permafrost region in Chajnantor Volcano, Atacama, northern Chile - Mena, Gabriela; Yoshikawa, Kenji; Schorghofer, Norbert; Pasten, Cesar; Ochoa, Felipe Agustin; Yoshii, Yuzuru; Doi, Mamoru; Miyata, Takeshi; Takahashi, Hidenori; Casassa, Gino; Sone, Toshio (My University, 2021)
Permafrost occurs in the high Atacama Desert, and its thermal state was characterized at a study site 5,075 m a.s.l., at the lower regional altitude boundary for permafrost. The permafrost body is about 5 m thick and located in the hydrothermal alteration zone. The freeze-thaw layer and upper part of the permafrost layer temperatures were measured at 0 to 39 cm depth at 1-cm resolution throughout the year. The upper 3 cm of the ground experienced more than 100 freeze-thaw cycles in 2019. The maximum thaw depth was 14 cm. No significant thermal offset is observed between the annual mean of the surface temperature and the top permafrost boundary. The 14-m borehole reveals that the geothermal gradient was quite high at 200 degrees C/km. In 2019 the seventy days of snow cover impacted the surface energy budget. Winter and summer snow conditions contribute to cooling the surface temperature regime in different ways.
Keywords: permafrost; freeze–; thaw cycle; high elevation; atacama; snow